PENGARUH PENAMBAHAN TEMPE TERHADAP KADAR PROTEIN DAN SIFAT ORGANOLEPTIK TORTILA - istinaroh istinaroh; siti aminah (Universitas Muhammadiyah Semarang, 2011)
Tortillas is a form of street food as a potential snack food. The combination of materials can be done to improve the nutritional value, such as tempeh. This study aims to determine the effect of soybean on protein content, water content and organoleptic properties of tortillas. Based on the analysis of protein levels more tortillas adding tempeh then tortillas increasing protein content, but this trend was not seen in the water content. Based on the good results of organoleptic tortillas taste, color, and aroma of the results showed that the highest value without the addition of tempeh.